Response of the COPD Assessment Tool in Stable and Postexacerbation Pulmonary Rehabilitation Populations. Issue 3 (May 2015) - Chaplin, Emma; Gibb, Michelle; Sewell, Louise; Singh, Sally
<x xml:space="preserve">Abstract</x> PURPOSE: The COPD Assessment Tool (CAT) has previously been shown to be a sensitive outcome measure for pulmonary rehabilitation (PR) in a stable population, but its utility in a postexacerbation PR population is unknown. The aim of this study was to investigate any differences in response to the CAT between stable and postexacerbation patients undertaking PR. METHODS: Patients attending a 7-week outpatient PR program completed a CAT questionnaire pre- and postrehabilitation. Patients referred for elective outpatient PR were compared with those who had been referred to PR following a hospital admission for an exacerbation. RESULTS: Two hundred consecutive patients completed the CAT questionnaire: 125 stable patients (74 male, mean age 71.1 ± 8.9 years, forced expiratory volume in 1 second [FEV1] 1.39 L ± 0.6, and body mass index [BMI] 28.5 ± 6.7 kg/m2) and 75 postexacerbation patients (23 male, mean age 70.6 ± 8.6 years, FEV1 1.16 L ± 0.5, and BMI 25.8 ± 7.3 kg/m2). A statistically significant difference between the stable and postexacerbation patient groups pre-PR CAT score (P = .05) was observed. There was no significant difference in post-PR CAT scores or change in CAT scores between the stable and postexacerbation groups. There was a significant difference in pre- and post-PR walking test results between the groups. The improvement in the Endurance Shuttle Walking Test (ESWT) in the stable group was greater (P < .05). CONCLUSIONS: Postexacerbation PR patients had a worse CAT score prior to PR when compared with a stable PR population, but both groups made improvements in CAT following completion of PR.